2023
DOI: 10.1021/acsami.3c01405
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Co-reduction of N2 and CO2 to Urea Using Bi2S3 Nanorods Anchored to N-Doped Reduced Graphene Oxide

Abstract: Producing "green urea" using renewable energy, N 2 , and CO 2 is a long-considered challenge. Herein, an electrocatalyst, Bi 2 S 3 /N-reduced graphene oxide (RGO), was synthesized by loading the Bi 2 S 3 nanorods onto the N-RGO via a hydrothermal method. The Bi 2 S 3 /N-RGO composites exhibit the highest yield of urea (4.4 mmol g −1 h −1 ), which is 12.6 and 3.1 times higher than that of Bi 2 S 3 (0.35 mmol g −1 h −1 ) and that of N-RGO (1.4 mmol g −1 h −1 ), respectively. N-RGO, because of its porous and open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…Catalyst [ref. ] Carbon source Nitrogen source Electrolyte Applied potential (vs. RHE) Urea yield rate Faradic efficiency PdCu/TiO 2 À 400 [1c] 1 bar CO 2 1 bar N 2 1 M KHCO 3 À 0.4 V 3.36 mmol g À 1 h À 1 8.92 % ZnMnÀ N,Cl [16] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.3 V 4.0 mmol g À 1 h 28.7 % Bi 2 S 3 /NÀ RGO [17] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.5 V 4.4 mmol g À 1 h À 1 7.5 % Bi/BiVO 4 [18] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.4 V 5.91 mmol g À 1 h À 1 12.55 % BiFeO 3 /BiVO 4 [19] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.4 V 4.94 mmol g À 1 h 17.18 % MoP [21] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.35 V 12.4 mg h À 1 mg cat À 1 36.5 % CuÀ Bi [14] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.4 V 0.45 � 0.06 mg L À 1 8.7 % � 1.7 % VoÀ CeO 2 -750 [27] 1 bar CO 2 50 mM KNO 3 0.1 M KHCO 3 + 50 mM KNO 3 À 1.6 V 943.6 mg h À 1 g À 1 -…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Catalyst [ref. ] Carbon source Nitrogen source Electrolyte Applied potential (vs. RHE) Urea yield rate Faradic efficiency PdCu/TiO 2 À 400 [1c] 1 bar CO 2 1 bar N 2 1 M KHCO 3 À 0.4 V 3.36 mmol g À 1 h À 1 8.92 % ZnMnÀ N,Cl [16] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.3 V 4.0 mmol g À 1 h 28.7 % Bi 2 S 3 /NÀ RGO [17] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.5 V 4.4 mmol g À 1 h À 1 7.5 % Bi/BiVO 4 [18] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.4 V 5.91 mmol g À 1 h À 1 12.55 % BiFeO 3 /BiVO 4 [19] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.4 V 4.94 mmol g À 1 h 17.18 % MoP [21] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.35 V 12.4 mg h À 1 mg cat À 1 36.5 % CuÀ Bi [14] 1 bar CO 2 1 bar N 2 0.1 M KHCO 3 À 0.4 V 0.45 � 0.06 mg L À 1 8.7 % � 1.7 % VoÀ CeO 2 -750 [27] 1 bar CO 2 50 mM KNO 3 0.1 M KHCO 3 + 50 mM KNO 3 À 1.6 V 943.6 mg h À 1 g À 1 -…”
Section: Discussionunclassified
“…Finally, the defect sites in Bi 2 S 3 /NÀ RGO and the synergistic effect between two components were beneficial to the formation of the CÀ N bond and further urea production. [17] Yuan et al integrated metallic Bi and semiconductor BiVO 4 into a novel Mott-Schottky BiÀ BiVO 4 heterostructures, achieving the urea yield rate of 5.91 mmol g À 1 h À 1 and FE of 12.55 % at À 0.4 V vs. RHE. Experimental, characterization and DFT calculations results indicated that the existing of space-charge region in the heterostructure interface of BiÀ BiVO 4 could facilitate the adsorption and activation of CO 2 and N 2 feedstocks on the produced local nucleophilic and electrophilic regions.…”
Section: The Strategies Of Activity Regulationmentioning
confidence: 99%
“…The reported protocols (Table 2, entries 25-33) attempt to enhance the chemisorption of both gases (CO 2 and N 2 ) on the catalyst. [201][202][203][204][205][206][207][208][209] Temperature-dependent desorption (TPD) measurements (amount of N 2 ) and Brunauer-Emmett-Teller adsorption-desorption isotherms (specific surface area) are very useful tools in identifying suitable catalyst candidates. In terms of mechanism, almost all protocols report the formation of the intermediate *NCON after reaction between *N 2 and *CO.…”
Section: Urea Production Starting From Dinitrogenmentioning
confidence: 99%
“…Although efforts have been made to electrochemically couple N 2 and CO 2 into urea, , there are still difficulties in inhibiting its industrial application due to low yield and poor selectivity of urea synthesis. The main problems of electrocatalytic urea synthesis are summarized as follows: (i) the inactive N 2 and CO 2 have a low mass transfer rate in an aqueous solution and extraordinarily weak chemical adsorption ability on the catalyst surface; , (ii) it is difficult to activate the highly stable CO bond (750 kJ mol –1 ) and NN bond (940.95 kJ mol –1 ), requiring high overpotentials; , (iii) the electrocatalytic synthesis of urea is greatly limited by side reactions, especially the hydrogen evolution reaction (HER) .…”
Section: Introductionmentioning
confidence: 99%